Security and safety - EDP Sciences (EDP Sciences, 2022)
High quality innovative and applicable research results in the information networks, integrated circuits, software engineering, industrial control, intelligent transportation, medical health, digital finance, social governance and other fields that involve the intersection of cyber security and functional safety.
Keywords: Computer security : Periodicals; Accidents : Prevention : Periodicals; Industrial safety : Periodicals